Extending Audit and Reporting Boundaries . - Wilkinson, James R.; Doney, Lloyd D. (The Accounting Review, 1965)
Auditing has been characterized by an extension of the audit examination into activities of the firm that were not previously included. In order that the audit by the independent accountant might better serve as an audit of management's performance, the examination by the accountant should include, an analysis of management's expectations for the coming year in the form of an anticipated statement of revenues and expenses, a pro-forma balance sheet, and a statement of expected sources and applications of funds. It should include a comparison of the audited financial statements for the current period with the anticipated statements prepared at the beginning of the period, indicating to some extent how well management has met its short-run objectives. It should also include use of a long-form type of report in which an analysis of the differences between expectations and realizations might be explained and evaluated. This would benefit, in some way, the management of the company, the stockholders and potential investors, creditors, competitors, and the government.